2003
DOI: 10.1115/1.1629309
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an H-Darrieus in the Skewed Flow on a Roof1

Abstract: Application of wind turbines on roofs of higher buildings is a subject of increasing interest. However, the wind conditions at the roof are complex and suitable wind turbines for this application are not yet developed. This paper addresses both issues: the wind conditions on the roof and the behavior of a roof-located wind turbine with respect to optimized energy yield. Vertical Axis Wind Turbines (VAWTs) are to be preferred for operation in a complex wind environment as is found on top of a roof. Since the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(100 citation statements)
references
References 5 publications
2
97
0
1
Order By: Relevance
“…They showed that the skewed flow increased the power coefficient of the H-rotor. This phenomenon was further confirmed by their wind tunnel experiments (Mertens et al, 2003) and hotwire measurement (Simão Ferreira, Van Bussel, & Van Kuik, 2006). Last, the VAWT can accept wind from any direction and can potentially be used in lieu of HAWT designs in urban and mountainous areas and gusty area (Riegler, 2003).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…They showed that the skewed flow increased the power coefficient of the H-rotor. This phenomenon was further confirmed by their wind tunnel experiments (Mertens et al, 2003) and hotwire measurement (Simão Ferreira, Van Bussel, & Van Kuik, 2006). Last, the VAWT can accept wind from any direction and can potentially be used in lieu of HAWT designs in urban and mountainous areas and gusty area (Riegler, 2003).…”
Section: Introductionmentioning
confidence: 69%
“…Email: yongsheng.lian@louisville.edu has decreased power output, making the VAWT more favorable on top of a roof. Mertens, Van Kuik, and Van Bussel (2003) numerically studied the performance of H-rotors in skewed flows. In their work computational fluid dynamics (CFD) was used to calculate the wind velocity over a rectangular model building.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on VAWTs was conducted until the end of the 1980s (especially in North America), when, due to the increasing success of the application of horizontal axis wind turbines (HAWTs) in Europe, it was discontinued. Yet, in the built environment, VAWTs present several advantages over the more common HAWTs, namely: low sound emission (a consequence of its operation at lower tip speed ratios), better esthetics due to its three-dimensionality (more suitable for integration in some architectural projects, since it follows the concept of volume of the building), its insensitivity to yaw and its increased performance in skew (see Mertens et al 2003;Simão Ferreira et al 2006). The present work aims at measuring the velocity field with dynamic stall at Reynolds numbers Re & 10 5 and k = 2, 3 and 4, conditions close to operational values for small VAWTs (below 2 kW rating) in full-scale urban applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand for VAWTs, depending on the configuration, the performance degradation due to skewed flow is generally lower and for H-VAWT (VAWT with two vertical blades connected to the central tower through one/more arms) configurations the power coefficient may even be enhanced. Experimental investigations on H-VAWT turbines have demonstrated an enhanced performance for relatively small tilt angles (up to 25 • − 30 • ) depending on the shape of the rotor, whereas a reduced performance is produced by higher skew values [11]. This benefit might be explained by the fact that VAWT blades sweep out a cylindrical surface, as opposed to a planar surface for HAWTs.…”
Section: Introductionmentioning
confidence: 92%